A Good Use of Philosophical Pleasures: A Conversation with Richard Rorty - Sergio Benvenuto (EJP import test, 2016)
This conversation, held in Rome on June 7, 1997, deals only marginally with psychoanalysis. Yet, as in our previously published interviews with philosophers, it situates Rorty’s appreciation of psychoanalysis in its philosophical context.
Keywords: Debate on Rawls; Foucauldian Left; Freudian Metaphors; Needs for Philosophy; utilitarianism